2011
DOI: 10.3923/pjbs.2011.441.448
|View full text |Cite
|
Sign up to set email alerts
|

High Vero Cell Density and Rabies Virus Proliferation on Fibracel Disks Versus Cytodex-1 in Spinner Flask

Abstract: To achieve higher titer of rabies virus higher density of host cells will need. In this study, capability of FibraCel disks packed in 500 mL spinner basket versus Cytodex-1 in 500 mL spinner flask was investigated for propagation of Vero cells and PV rabies virus proliferation. Minimal Essential Medium (MEM) + 10% Foetal Calf Serum (FCS) and Virus Production- Serum Free Medium (VP-SFM) +4 mM L-glutamine were used in growth phase and MEM+ 0.2% Bovine Serum Albumin (BSA) and VP-SFM were used in virus production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Infection of the BHK21 cell line showed 100% positivity of infected mice brain suspension resulting in specific CPE of RABV by the second day postinfection as cell rounding followed by cell lysis and detachment of the cell sheet. These results match what was described by Consales et al (1990) , Knezevic (2008) , and Hassanzadeh et al (2011) , who found that RABV could be harvested from BHK cell culture with similar findings at around 48 hours of infection.…”
Section: Discussionsupporting
confidence: 91%
“…Infection of the BHK21 cell line showed 100% positivity of infected mice brain suspension resulting in specific CPE of RABV by the second day postinfection as cell rounding followed by cell lysis and detachment of the cell sheet. These results match what was described by Consales et al (1990) , Knezevic (2008) , and Hassanzadeh et al (2011) , who found that RABV could be harvested from BHK cell culture with similar findings at around 48 hours of infection.…”
Section: Discussionsupporting
confidence: 91%
“…Also, transmission can be via the saliva that is the major source of virus spread ( 5 ). Rabies disease is endemic in the wild life of our country, therefore domestic animals are frequently infected while, enhancing cases of animal bite and scattering of disease virus in most provinces of Iran, declare a need to pay more attention to controlling this disease ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, in case of very fragile cells, in particular cells infected by viruses for virus production, it was shown that the replacement of solid carriers such as Cytodex 1 by Fibra-cel discs, in which the cells are immobilized, led to higher (rabies) virus production probably because of reduced cell loss caused by bead collisions [39]. On the other hand, cells can also be protected from turbulences at high agitation by addition of thickening agents (polymers to increase viscosity) [40].…”
Section: (I) Microcarrier Technology: Basicsmentioning
confidence: 99%